Modernitas Pesantren dan Kesakralan Pernikahan dalam Upacara Rahmat Pura - Zulaili, Iin Nur (FIKRAH, 2020)
The phenomena of Mass Marriage is often the case in Indonesia, but the mass marriage with a certain ceremony has been different presented of religious behavior in the community layer. This article discusses about “Rahmat Pura” festivals organized by SPMAA Foundation in Lamongan once a year. The Modernization theory will be examining by the tradition of Rahmat Pura, which is the processing, lasting, and enduring in this modern era. The autors use qualitative methods of conducting intensive interviews with organizers as well as festival participants. The results showed that the interconnectedness between students (santri muslim) and the devotion for pesantren in the era of Islamic modernity remains a preserved tradition.